2017
DOI: 10.1080/02713683.2017.1339806
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antimicrobial Peptides by Uveal and Cutaneous Melanoma Cells and Investigation of Their Role in Tumor Cell Migration and Vasculogenic Mimicry

Abstract: Aims: Antimicrobial peptides (AMPs) have been implicated in the pathogenesis of several cancers, although there is also evidence suggesting potential for novel, AMP-based anti-tumour therapies. Discerning potential roles of AMPs in tumour pathogenesis may provide valuable insight on mechanisms of novel AMP-based anti-tumour therapy. Methods: mRNA expression of the AMPs α defensin (HNP-1); cathelicidin (LL-37); and β defensins (hBD-1, hBD-2, hBD-3, hBD-4) in human uveal and cutaneous melanoma cell lines, prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Although this pattern appears as PAS +ve thin lines by light microscopy, Frenkel et al described that these structures appeared as hollow channels with blood circulation in their lumens by laser scanning confocal angiography in a choroidal melanoma [ 31 ]. Moreover, Manarang JC et al described that highly aggressive melanoma cells cultured in 3 dimensional matrix gel induced the formation of VM with characteristic looping patterns that can transmit fluids, while less aggressive cells did not produce these VM patterns when grown on similar conditions [ 32 ]. Interestingly, it has been also suggested that VM not only promotes tumor growth but also facilitate lymphovascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Although this pattern appears as PAS +ve thin lines by light microscopy, Frenkel et al described that these structures appeared as hollow channels with blood circulation in their lumens by laser scanning confocal angiography in a choroidal melanoma [ 31 ]. Moreover, Manarang JC et al described that highly aggressive melanoma cells cultured in 3 dimensional matrix gel induced the formation of VM with characteristic looping patterns that can transmit fluids, while less aggressive cells did not produce these VM patterns when grown on similar conditions [ 32 ]. Interestingly, it has been also suggested that VM not only promotes tumor growth but also facilitate lymphovascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LL-37 on myeloid cells in dermis is correlated with levels of proinflammatory cytokines such as IL-23p19, IL-17A, and TNF-α [ 6 , 7 ], which could promote tumor progression via angiogenesis in melanoma and non-melanoma skin cancers [ 8 , 9 , 10 , 11 ]. Moreover, LL-37 is expressed in melanoma cells, potentially promoting their own proliferation, migration and invasion by autocrine and/or paracrine fashions [ 11 , 12 , 13 ]. Notably, dermal expression of LL-37 is increased in parallel with dermal invasion of tumor cells in skin cancers [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%